ROLE OF HOST RESISTANCE AND PLANTING TIME IN PROGRESSION OF WHITE RUST AND YIELD OF MUSTARD - G. S. SAHARAN, B. S. LAKRA AND (Indian Phytopathology, 2002)
White rust (Albugo candida) progressed rapidly on a susceptible cultivar, RH 30 of mustard when there was RH ;;;,65 per cent and average temperature ~ 15°C. Staghead infection required higher RH besides low temperature. On cv RH 30 with delay in planting time from 15 September to 30 November 1985, there was sharp increase in infection of leaf as well as staghead phases. Plantings in December were more favourable for staghead formation. The resistant nature of RC 781 sustained infection even during epidemics. Yield losses in early sown crop could be avoided because of high temperature C> 15°C), low RH «60 per cent) and absence of rainfall which were unfavourable for pathogen and favourable for plant growth.